3D structure of muscle dihydropyridine receptor - Montserrat Samsó (PAGEPress Publications, 2015)
Excitation contraction coupling, the rapid and massive Ca2+ release under control of an action potential that triggers muscle contraction, takes places at specialized regions of the cell called triad junctions. There, a highly ordered supramolecular complex between the dihydropyridine receptor (DHPR) and the ryanodine receptor (RyR1) mediates the quasi‐instantaneous conversion from T‐tubule depolarization into Ca2+ release from the sarcoplasmic reticulum (SR). The DHPR has several key modules required for EC coupling: the voltage sensors and II‐III loop in the alpha1s subunit, and the beta subunit. To gain insight into their molecular organization, this review examines the most updated 3D structure of the DHPR as obtained by transmission electron microscopy and image reconstruction. Although structure determination of a heteromeric membrane protein such as the DHPR is challenging, novel technical advances in protein expression and 3D labeling facilitated this task. The 3D structure of the DHPR complex consists of a main body with five irregular corners around its perimeter encompassing the transmembrane alpha 1s subunit besides the intracellular beta subunit, an extended extracellular alpha 2 subunit, and a bulky intracellular II‐III loop. The structural definition attained at 19 Å resolution enabled docking of the atomic coordinates of structural homologs of the alpha1s and beta subunits. These structural features, together with their relative location with respect to the RyR1, are discussed in the context of the functional data.